0601 Long-term Effects Of Solriamfetol On Quality Of Life In Participants With Excessive Daytime Sleepiness Associated With Narcolepsy Or Obstructive Sleep Apnea. (12th April 2019) - Weaver, Terri; Pepin, Jean-Louis; Schwab, Richard; Shapiro, Colin; Hedner, Jan; Ahmed, Mansoor; Foldvary-Schaefer, Nancy; Strollo, Patrick J; Mayer, Geert; Sarmiento, Kathleen; Baladi, Michelle; Bron, Morgan; et al.
Abstract: Introduction: Solriamfetol, a selective dopamine and norepinephrine reuptake inhibitor, demonstrated long-term (up to 52 weeks) efficacy in participants with excessive daytime sleepiness (EDS) associated with narcolepsy or obstructive sleep apnea (OSA). These analyses evaluated long-term effects of solriamfetol on quality of life (QoL) measures. Methods: Participants with narcolepsy or OSA who completed previous solriamfetol studies were eligible. This study included 2-week titration followed by a maintenance phase of up to 50 weeks (stable dose 75, 150, or 300 mg). QoL assessments included the Functional Outcomes of Sleep Questionnaire short version (FOSQ-10), Work Productivity and Activity Impairment Questionnaire: Specific Health Problem (WPAI:SHP), and 36-Item Short Form Health Survey version 2 (SF-36v2). Mean (SD) change from baseline throughout the study was evaluated for the overall safety population and by subgroup (OSA or narcolepsy). No formal statistical testing was performed. Safety was assessed. Results: There were 643 participants (417 OSA, 226 narcolepsy) in the safety population. Increases in mean FOSQ-10 total score from baseline [mean change (SD) of 3.7 (3.0)] were sustained for the duration of treatment with solriamfetol; magnitude of change was similar between narcolepsy and OSA. On WPAI:SHP, participants reported a minimum 25% reduction (improvement) from baseline for % activity impairment outside of work, % impairment while working (presenteeism), and % overall work impairment due to the problem; results were generally similar for each subgroup. For SF-36v2, both physical and mental component summary scores showed increases in the health state of participants from baseline [mean change (SD) of 3.1 (6.9) and 4.3 (8.4), respectively]; these improvements were maintained for the duration of the study. Common adverse events (≥5%) included headache, nausea, insomnia, nasopharyngitis, dry mouth, anxiety, decreased appetite, and upper-respiratory-tract infection, and were similar in narcolepsy and OSA; 27 participants (4.2%) had ≥1 serious adverse event. Conclusion: Solriamfetol demonstrated sustained improvements in QoL measures for up to 52 weeks in participants with EDS associated with narcolepsy or OSA. Safety was similar to prior solriamfetol studies. Support (If Any): Jazz Pharmaceuticals